2012
DOI: 10.1364/ol.37.003072
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband ultraviolet photodetector based on MgZnO and NPB heterojunction

Abstract: An ultraviolet photodetector was fabricated based on Mg0.07Zn0.93O heterojunction. N, N'-bis (naphthalen-1-y1)-N, N'-bis(pheny) benzidine was selected as the hole transporting layer. I-V characteristic curves of the device were measured in the dark and under the illumination of 340 nm UV light with density of 1.33 mW/cm2. The device showed a low dark current of about 3×10(-10) A and a high photo-dark current ratio of 1×10(5) at -2 V bias. A narrowband photoresponse was observed from 300 to 400 nm and centered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Recently, solar-blind photodetectors (SBPDs) have become attractive for their versatile applications in missile warning, space-to-space communications, and flame monitoring [1][2][3][4]. MgZnO is a promising material for fabricating SBPDs due to the large tunable bandgap energy (3.3-7.8 eV) [5], high radiation hardness [6], and low growth temperature [7]. Compared to p-n, p-in and Schottky structures, a metal-semiconductor-metal (MSM) [8][9][10][11] photodetector is the critical component in receiver optoelectronic integrated circuits (OEICs) because of its lower intrinsic capacitance and suitability for monolithic integration.…”
mentioning
confidence: 99%
“…Recently, solar-blind photodetectors (SBPDs) have become attractive for their versatile applications in missile warning, space-to-space communications, and flame monitoring [1][2][3][4]. MgZnO is a promising material for fabricating SBPDs due to the large tunable bandgap energy (3.3-7.8 eV) [5], high radiation hardness [6], and low growth temperature [7]. Compared to p-n, p-in and Schottky structures, a metal-semiconductor-metal (MSM) [8][9][10][11] photodetector is the critical component in receiver optoelectronic integrated circuits (OEICs) because of its lower intrinsic capacitance and suitability for monolithic integration.…”
mentioning
confidence: 99%
“…3(a)). [46] The dark I-V curve of the detector indicated that the device has a good rectifying property and a relatively low dark current (I d : 3 × 10 −10 A).…”
Section: Wavelength/nmmentioning
confidence: 95%
“…Responsivity/(A/W) [46] PN-junction photodetector is supposed to be the most suitable choice for future applications in consequence of its fast responding speed, low dark current, and working without applied bias. However, P-type doping is still a big challenge to ZnO-based semiconductor.…”
Section: Wavelength/nmmentioning
confidence: 99%
“…[1,2] In the initial stage, inorganic narrow-bandgap semiconductors like Si or GaAs were frequently applied for UV detection with filters to cut off the long wavelengths, while they exhibited inferior radiation hardness properties and high dark current. [3−5] Later on, widebandgap semiconductors such as GaN, [6,7] AlGaN, [8] AlN, [9] ZnO, [10] MgZnO, [11,12] SiC [13] and diamond [14] were gradually introduced, based on which photosensors with UV selective response have been largely reported. However, photodetectors based on individual inorganic wide-bandgap semiconductors would require complicated fabrication processes, such as metalorganic chemical vapor deposition (MOCVD) and molecular beam epitaxy (MBE), leading to a high cost.…”
mentioning
confidence: 99%
“…We have now developed a device based on N,N'-bis(naphthalen-1-yl)-N,N'-bis (phenyl) benzidine (NPB) [12] and fullerene C 60 . The chemical structures of NPB and C 60 are shown in Fig.…”
mentioning
confidence: 99%